Think inside the jar - Winberg, Irma (2016)
The interest for cooking and origin of ingredients in food is increasing in Sweden. But, the consumption of processed food is also increasing, resulting in dishes where the origin of the ingredients often is unknown. Sweden is one of the countries with the highest consumption of prepared jarred baby food. Studying the labels, you find the ingredients are of unknown origin neither produced nor manufactured in Sweden. In autumn of 2015, a company was established with the aim of producing baby food made from Swedish raw materials. The entrepreneur is trying to establish herself on the Swedish baby food market, a market currently dominated by world leading brands. The entrepreneur has no education when it comes to food or business, only an incentive to provide high quality baby food. She is therefore dependent on competence and knowledge available in the surrounding context. The aim of this study is to investigate how the context interacts with the entrepreneurial process of a micro enterprise and how entrepreneurs make decisions for developing companies based on context through entrepreneurial marketing. The study consists of case studies of longitudinal research design. Three interviews during three months have been done with the particular entrepreneur so as to study the interaction between the context and the entrepreneurial process in this micro enterprise, and two interviews have been carried out with two actors, that the entrepreneur stated as important parts of her context. The theoretical framework is conducted on previous research by studying entrepreneurship and the entrepreneurial process together with context, its impact on the entrepreneurial process and how this interaction functions and fluctuates. Entrepreneurial marketing is added to study how it is used to reach the customers the entrepreneur seek. The results of the study show that context affects the entrepreneurial process, and vice versa. The biggest impact is the social context through unpredictable events in the social network and the family, which has been demonstrated by the selection of longitudinal research design. The study also shows that an entrepreneur in a start-up micro enterprise believes in a direct increase in demand for the product. However the interaction time is longer than expected and the best way to increase awareness of the product is by communicating with customers, resulting in entrepreneurial marketing.